EXPERIMENTAL DETERMINATION OF THE WETTED AREA OF A FALLING FILM ON THE OUTSIDE OF HORIZONTAL TUBES USING IMAGE PROCESSING AND HEAT TRANSFER ANALYSIS - Onan, Cenk; Ozkan, Derya B. (BEGELL HOUSE INC, 2017)
Falling film is observed in closed-type cooling towers, evaporative condensers, and in absorption cooling. In this study, the aim was to increase the amount of evaporating water on the tube surface during the falling of the film. To increase the area of wetness, grooves of different shapes were used, which were placed longitudinally or helically on horizontal tubes. The groove geometries were triangular, trapezoidal, round, and square. In the experiments, the area of wetness was measured by generating falling film-type flow on horizontal tubes with these four different groove geometries. The falling film-type flow was generated using dyed water to measure the area of wetness. Photographs were taken using a high-speed camera to determine the area of wetness in the tubes. The photographs were processed using MATLAB, and it was concluded that the tube of helical trapezoidal geometry had the maximum rate of wet area of 74% and that the tube of longitudinal trapezoidal groove geometry had the minimum rate of 46%. Afterwards, the amount of evaporating water, heat convection coefficients, and Nusselt number values were determined. The results indicated that as the temperature of the feeding water increased, the amount of evaporating water also increased. The Nusselt correlation was observed at different temperatures of feeding water between 30 degrees C and 40 degrees C and depending on the Re-w and Re-a of the falling film. It was determined that while Re-w was between 100 and 350, the observed heat convection coefficient was between 15 and 55 W/m(2) K for the simultaneous heat and mass transfer.
Keywords: heat transfer; horizontal tube; falling film; image processing; groove; FLOW; EVAPORATION; Thermodynamics